The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/aap.0000000000000816
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of 400 mg Locally Infiltrated Ropivacaine After Total Knee Arthroplasty Without Perioperative Tourniquet Use

Abstract: This study was registered at Netherlands Trial Registry (http://www.trialregister.nl), trial ID NTR6306.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(37 reference statements)
3
4
0
Order By: Relevance
“…Local anesthetic administered intravasally or in excessive doses can lead to toxic side effects on the cardiovascular and central nervous system, mimicking OI symptoms. Several studies 36–38 in TKA patients using identical ropivacaine doses to ours reported peak free ropivacaine concentrations well below previously proposed toxic thresholds. Previous studies investigating OI using no LIA 11,14,33 or LIA with bupivacaine 3,10 report similar incidences as ours.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Local anesthetic administered intravasally or in excessive doses can lead to toxic side effects on the cardiovascular and central nervous system, mimicking OI symptoms. Several studies 36–38 in TKA patients using identical ropivacaine doses to ours reported peak free ropivacaine concentrations well below previously proposed toxic thresholds. Previous studies investigating OI using no LIA 11,14,33 or LIA with bupivacaine 3,10 report similar incidences as ours.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, there was no difference in bleeding nor perioperative fluid status between OT and OI or severe OI patients. Pre-and postoperative anemia is common in patients undergoing TKA 34 [36][37][38] in TKA patients using identical ropivacaine doses to ours reported peak free ropivacaine concentrations well below previously proposed toxic thresholds. Previous studies investigating OI using no LIA 11,14,33 or LIA with bupivacaine 3,10 report similar incidences as ours.…”
Section: à29supporting
confidence: 63%
“…Moreover, serum ropivacaine levels following high dosage PNB and local infiltration analgesia have in other studies been found to be below the potential level of toxicity 12‐14 . However, the risk of LAST should always be contemplated very carefully with all regional anaesthesia techniques.…”
Section: Introductionmentioning
confidence: 98%
“…In this study, the initial dose of ropivacaine for LIA was less than the maximal dose (225 mg) indicated by drug label [46], however, when combined with ACB bolus, the total dose (240 mg) of ropivacaine was slightly higher than recommended. However, previous studies have shown that injecting a much higher dose of ropivacaine in intra-articular LIA, than used in this study, is safe, with plasma levels below systemic toxic threshold [4750]. Moreover, there was a 60 min interval between injections, which reduced plasma levels.…”
Section: Discussionmentioning
confidence: 80%